2021
DOI: 10.1186/s13104-021-05443-9
|View full text |Cite
|
Sign up to set email alerts
|

A pilot trial of human amniotic fluid for the treatment of COVID-19

Abstract: Objective Vertical transmission from SARS CoV-2-infected women is uncommon and coronavirus has not been detected in amniotic fluid. Human amniotic products have a broad immune-mediating profile. Observing that many COVID-19 patients have a profound inflammatory response to the virus, we sought to determine the influence of human amniotic fluid (hAF) on hospitalized patients with COVID-19. Results A 10-patient case series was IRB-approved to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Generally, hAF collected during the routine amniocentesis or cesarean section are devoid of any cellular products. Increasing evidences indicate that human amniotic membrane and hAF can alleviate inflammation, have antimicrobial properties, and confer a low risk of immunogenicity ( 21 , 43 , 44 ). The AF of normal human (week 17–20) and rat (E16-17) can improve survival and growth of neuronal and non-neuronal cells as culture media ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, hAF collected during the routine amniocentesis or cesarean section are devoid of any cellular products. Increasing evidences indicate that human amniotic membrane and hAF can alleviate inflammation, have antimicrobial properties, and confer a low risk of immunogenicity ( 21 , 43 , 44 ). The AF of normal human (week 17–20) and rat (E16-17) can improve survival and growth of neuronal and non-neuronal cells as culture media ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that chick embryo AF can promote peripheral nerve regeneration in rats ( 19 ) and rat AF can prevent intraperitoneal adhesion formation in surgical operation ( 20 ). A more recent study showed that human AF (hAF) reduces C-reactive protein, a marker of inflammation, and improved clinical outcomes in hospitalized patients with COVID-19 after intravenous 10 ml hAF without obvious adverse events ( 21 ), indicating an immune-mediating role of hAF. Previously, we demonstrated that chick early amniotic fluid (ceAF) can effectively rescue heart dysfunction after ischemic injury in swine and mouse models ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the total lack of any observed maternal to fetal transmission of COVID-19 suggested that placental tissues, including AF, may have a protective effect. One report describes a 10 patient study consisting of patients with hospital-diagnosed COVID-19: six patients received intravenous delivery of cfAF, which resulted in significantly improved morbidity and mortality, and no adverse effects [ 82 ]. Another group performed similar studies in COVID-19 patients with mild-moderate symptoms, also by injecting cfAF intravenously.…”
Section: Current Clinical Studies/applications Using Cell-free Amniot...mentioning
confidence: 99%
“…However, it is unclear how removal of potentially pre-existing antibody may juxtapose with subsequent donor immunity and final outcomes. Another unique but related approach has been piloted by Selzman et al [ 274 ] with the use of therapeutic donor human amniotic fluid. Given intravenously, there is the potential for immunomodulating effects on active COVID-19, but when donated by a convalescent mother who suffered active infection prior to birth, there is also the potential for transfer of maternal virus-directed IgG for a form of passive therapy.…”
Section: Covid-19mentioning
confidence: 99%